Hubungan antara Kualiti Perkhidmatan Laman Web E-Dagang Terhadap Kecenderungan Pembelian dalam Kalangan Pembeli: Kajian Kes di Kedai Perniagaan Sukan Al-Ikhsan - Intan Alias; Fazian Hashim (Research in Management of Technology and Business, 2024)
Online shopping has become a trend over time now. This has made the website a shopping place for the community today. Due time saving and energy conservation, client choose easier ways to acquire products by performing online purchase. This study aims to investigate the extent to which the service quality provided by e-commerce merchants can influence buyers to increase the tendency to purchase from the same merchant. The target respondents of this study have been randomly selected among those clients that made purchases on the e-commerce website at the Al-Ikhsan sportswear store. This research used E-Servqual to evaluate service quality based on 5 dimensions, namely website design, reliability, responsiveness, trust and personalization. Quantitative research method has been adapted in this study and survey questionnaires has been distributed for data collection purposes. Total of 384 clients have been identified as respondents for the study.